A man for all seasons : a play in two acts - Bolt, Robert (New York : Vintage Books, 1990)
The classic play about Sir Thomas More, the Lord chancellor who refused to compromise and was executed by Henry VIII. The story in play form of the conflict between Sir Thomas More & Henry VIII.
Keywords: More, Thomas, -- Sir, Saint, -- 1478-1535 -- Drama; Great Britain -- History -- Henry VIII, 1509-1547 -- Drama